2018
DOI: 10.1038/s41419-017-0209-y
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of senescence escape by the cdk4–EZH2–AP2M1 pathway in response to chemotherapy

Abstract: Senescence is a tumor suppressive mechanism that induces a permanent proliferative arrest in response to an oncogenic insult or to the genotoxic stress induced by chemotherapy. We have recently described that some cells can escape this arrest, either because senescence was incomplete or as a consequence of a phenotypic adaptation. Malignant cells which resisted senescence emerged as more transformed cells that resist anoikis and rely on survival pathways activated by Akt and Mcl-1. In this study, we further ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 34 publications
2
48
0
Order By: Relevance
“…In addition, some studies have preliminarily explored the mechanisms of AP2M1. Mélanie Le Duff et al [17] showed that the downregulation of AP2M1 in cancer cells signi cantly reduced the sensitivity to soluble signals generated from senescent cells, thereby inhibiting cell invasion. Further, following apoptosis induction, AP2M1 expression varies in different types of cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies have preliminarily explored the mechanisms of AP2M1. Mélanie Le Duff et al [17] showed that the downregulation of AP2M1 in cancer cells signi cantly reduced the sensitivity to soluble signals generated from senescent cells, thereby inhibiting cell invasion. Further, following apoptosis induction, AP2M1 expression varies in different types of cells.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that this suppression functions as an adaptive mechanism in response to chemotherapy-induced -senescence (CIS) (7,9). We have described that cancer cells can escape senescence and emerge as more transformed cells that resist anoikis and are more invasive (14)(15)(16)(17). In addition, we have also shown that cells having an incomplete senescence response are characterized by a reduced expression of CD47 (17).…”
Section: Introductionmentioning
confidence: 94%
“…In this condition, we and others have shown that senescence relies on p21waf1 and it is not obvious that this protein is always acting as an inhibitor of cancer progression. Using different experimental models, we have shown that cancer cells enter senescence in response to chemotherapy but that persistent cells are able to escape this suppressive arrest . Senescence escape leads to the emergence of more transformed clones with enhanced potential for migration.…”
Section: Different Outcomes For Different Senescence Typesmentioning
confidence: 99%
“…We and others have also shown that these arrested cells and the proteins they secrete play a key role in chemotherapy resistance, allowing the generation of more aggressive cells in response to genotoxic treatments. [16][17][18][19] For instance, important results indicate that Wnt activation induces the dedifferentiation of senescent cells, the reactivation of cell cycle progression, and the generation of subpopulations with higher tumor initiation potential. [20] This oncogenic activity of the SASP is normally restrained by Rb-Suv39 signaling or p53.…”
Section: The Senescence-associated Secretory Phenotypementioning
confidence: 99%
See 1 more Smart Citation